Early intracellular signaling events induced by in vitro metreleptin administration in cardiac myocytes and uterine smooth muscle cells - Choi, S K; Park, S; Choi, Y; Moon, H-S (Cellular and Molecular Biology, 2015)
Intracellular signaling pathways regulated by leptin have largely been studied in metabolically important organs such as adipose tissue and peripheral blood mononuclear cells, suggesting that leptin plays a key role in pathophysiology of insulin resistance. However, whether synthetic analog of leptin, metreleptin, has similar effects on cardiac myocytes (CM) and uterine smooth muscle cells (USMC) has not yet been studied. Hence, in order to address these questions, we extended previous observations and investigated in vitro signaling study whether metreleptin may activate key signaling pathways. We observed that metreleptin activates Jak2 and STAT3 signaling pathways in dose- and time-dependent manner in CM and USMC. Also, we found that metreleptin increases ERK1/2, JNK and/or p38 phosphorylation in CM. In vitro metreleptin administration also increased ERK1/2 and/or p38 phosphorylation in USMC. By contrast, JNK was not regulated by in vitro metreleptin administration in USMC. Moreover, metreleptin-activated all signaling pathways were blocked by pre-treatment of PD98095 (ERK inhibitor), SB203580 (p38 inhibitor) and/or SP600125 (JNK inhibitor), respectively. Finally, metreleptin increased cell size (hypertrophy) in both CM and USMC. Our data provide novel insights into the role of Jak2, STAT3, ERK1/2, JNK and/or p38 as probable mediators of the action of leptin in regulating hypertrophy in CM and USMC.